Primary Esophageal Lymphoma: A Histopathological Experience from Two Tertiary Hospitals, Western Saudi Arabia - Jaudah Al-Maghrabi; Sahar Al-Maghrabi (Gastroenterology Research and Practice)
Background. Primary esophageal lymphoma (PEL) is a rare disorder. The objective of this study was to document the clinicopathological features of PEL at two tertiary hospitals in the western region of the Kingdom of Saudi Arabia. Methods. All PELs diagnosed between May 2002 and June 2022 were retrieved. Histopathological and immunohistochemical slides were reviewed. Additional immunohistochemistry stains were performed in selected cases. Follow-up data were collected. Results. There were only eight cases of PEL in the records of the two hospitals. The age of the patients ranged between 50 and 74 years (median 62 years and mean 62.5 years). There were six males (80%) and two females (20%). None of the patients were immunocompromised or had human immunodeficiency virus (HIV) infection. The clinical manifestation included dysphagia and loss of weight. Six cases were diffuse large B-cell lymphoma (DLBCL), and two were low-grade mucosa-associated lymphoid tissue lymphoma. Conclusion. PEL is an extremely rare disease with male predominance. DLBCL is the most common pathological type in our community. There was no relation to immune status or HIV infection in this series. Clinical presentations were typically dysphagia with weight loss. Further reporting of PEL cases might help explain this disease and improve its diagnosis and management.